THE ROLE OF PAYMENT AND PAYMENT FLOWS IN DETERMINING THE NATURE OF THE PAYMENT CIRCUIT (American Journal of Business Management, Economics and Banking, 2025)
This scientific article discusses the scientific and practical aspects of the nature of payment circulation, the problems related to it and ways to solve them. It is clearly stated that determining the nature of the payment circulation requires determining the nature of the payment, and the possibility of determining the nature of the "payment circulation" without determining the nature of the "payment".